PENERAPAN METODE PEMBELAJARAN DOUBLE LOOP PROBLEM SOLVING DALAM MENINGKATKAN HASIL BELAJAR PPKn KELAS VIII SMP NEGERI 2 TELUKDALAM - Seinda Gaurifa (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2024)
The problem in this research is that student learning outcomes tend to be low. The aim of the research is to determine the application of the double loop problem solving learning method to improve PPKn learning outcomes for class VIII SMP Negri 2 Teluk for the 2023/2024 academic year. This type of research is a class action lawsuit (PTK). This research targeted 30 class VIII students and the results showed that student learning outcomes increased. This is shown by an increase in student learning outcomes in Cycle I which has an average score of 1. Cycle II has a completeness level of 100% with a score of 64, a completeness level of 56.67%, and an average score of 78.17. By applying the double loop problem solving learning method, students are trained to design discoveries, solve problems, and build good working relationships between students. It can be concluded that the application of the "Double Loop Problem Solving" learning method will improve PPKn learning outcomes for class VIII SMP Negri 2 Teluk for the 2023/2024 academic year. The suggestions put forward by researchers are: 1) Students should play an active role in learning activities. Learning outcomes will definitely improve if you are actively involved in learning. 2) Teachers should use the "double loop problem-solving" learning method as an alternative to improve learning outcomes and involve students in the learning process. 3) Schools should encourage subject teachers to adopt learning methods.